2005
DOI: 10.1590/s0004-282x2005000500014
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin-glycoproteins associated in congenital muscular dystrophy: immunohistochemical analysis of 59 Brazilian cases

Abstract: o nc l u s i o n :T h e re is a greater relationship between merosin and the former proteins; among MP-CMD patients, no remarkable immunohistochemical/phenotypical correlations were found, although the reduced expre ssion of β-DG had showed statistically significant correlation with severe phenotype and marked fibro s i s on muscular biopsy.KEY WORDS: congenital muscular dystro p h y, merosin, dystro p h i n -g l y c o p roteins associated complex, sarc o g l ycan complex, dystroglycan complex.Complexo distro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
6
0
3
Order By: Relevance
“…Its expression influences the peripheral myelinogenesis 83 . however, peripheral motor nerves involvement has not been found in Brazilian children with MDC 1A 84,85 and this fact might be due to the type and location of the mutation 84 .…”
Section: Merosin-deficient Congenital Muscular Dystrophy: Mdc1amentioning
confidence: 89%
“…Its expression influences the peripheral myelinogenesis 83 . however, peripheral motor nerves involvement has not been found in Brazilian children with MDC 1A 84,85 and this fact might be due to the type and location of the mutation 84 .…”
Section: Merosin-deficient Congenital Muscular Dystrophy: Mdc1amentioning
confidence: 89%
“…Early studies suggested that laminin ␣2 abnormalities accounted for 40% of all CMD cases in France and the United Kingdom, 42 but the frequency is now known to have regional variability. 43 Even so, abnormal laminin ␣2 is still often cited to be the most common single form of CMD. 7,8,18 Previous studies have shown altered ␣7-integrin expression in patients with CMD.…”
Section: Collagen VI Abnormalitiesmentioning
confidence: 99%
“…A Brazilian study diagnosed merosin-deficiency in around 40% of CMD patients (Ferreira, Marie et al 2005), while this diagnosis accounted for only 8% of CMD patients in an Australian study (Peat, Smith et al 2008). Differences in CMD ascertainment criteria may be partly responsible but it is likely there are true differences in disease incidence in different populations.…”
Section: Frequency Of Diagnosis Of Less Common Types Of MDmentioning
confidence: 99%
“…Differences in CMD ascertainment criteria may be partly responsible but it is likely there are true differences in disease incidence in different populations. Similarly, different rates of collagen VI diagnoses have been observed, ranging from 8% in Australia (Peat, Smith et al 2008) to 1.7% in Brazil (Ferreira, Marie et al 2005). …”
Section: Frequency Of Diagnosis Of Less Common Types Of MDmentioning
confidence: 99%